Kultura pomorska na terenie Rumi. W 110 rocznicę pierwszych odkryć - Fudziński, Mirosław (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
Rumia is siluatcd in the north-west of Trójmiasto (Gdańsk, Gdynia, Sopot) and stretches along the border of two landscape forms: high edge of Pojezierze Kaszubskie highlands and Pradolina Kaszubska, that is the channel of Reda and vast heath regions known as Mostowe Biota (Bridge Mud) and Chylońskie swamps. In the article we present archaeological material uncovered in the territory of Rumia and belonging to the Pomeranian culture, coming from the Hallstatt and Laten period. The oldest documented in literature recovery took place in the year 1887 when accidental finds of chest graves (Ruinia, site no. 22), including numerous cinerary urns took place, the precise localisation of the finding being unknown. Similar findings took place in the years 1907, 1908, 1913 and 1916. These were also accidental recoveries of chest graves. In the year 1922 archaeological expedition from Poznań conducted surface examinations in Rumia, and traces of settlement from the described periods were observed (Rumia, sites no. 19 and 20). In 1935 on the field called „Markowiec” (Rumia, site no. 1) a chest grave including eight face urns and a bulbous vessel were accidentally uncovered. The case of accidental finding of a few graves of Pomeranian culture population which took place in the year 1941 (Rumia, site no. 5) is also known. After the war findings of Pomeranian culture chest graves took place on the premises of the Metallurgical Plant in Zagórze, in the year 1950; near Sobieski street in the place known as „Biała Rzeka” (White River) where three chest graves were found, in the year 1954 (Rumia, site no. 21); and in a sand excavation situated near the road leading from Rumia to Gdynia, in the year 1957 (Rumia-Janowo, site no. 2). Further findings took place in the year 1970 (Rumia, site no. 18) and (Rumia-Janowo, site no. 4), in 1971-1972 (Rumia-Janowo, site no. 5), in 1979 on „Markowiec Hill” (Rumia, site no. 1) and again in 1985 r., (site no. 18). In the 80 ties surface examinations within the project of Archaeological Picture of Poland. The territory of Rumia is situated within two rectangulars: 7-41 and 7-42. Until now only one of them has been examined. Among newly uncovered sites our attention is focused on two settlements from the early Iron Age (site nos. 16 and 17). In the year 1996, during researches conducted in the church and cemetery in Church street (Rumia, site no. 24), at the depth of about 120 cm fragment of ceramics from early Iron Age was found. At present in Rumia there are nine sites known from Pomeranian culture finds. Apart from that archival information about earlier recoveries is known, and a part of the described there materials has been preserved. Their number will increase after the surface examinations on the territory covered by the rectangular 7-41 are conducted, where the western part of the town is situated. All the above sites belong to an observable in the decline of Hallstatt period microregion situated on the west of Kępa Oksywska and further in the direction of Gdynia and Gdańsk. This microregion is isolated from Pojezierze Kaszubskie macroregion.